Effects of Exercise on The Human Body - Буранов Илхомжон Комилович (Scientific Trends, 2024)
Exercise has a significant impact on a person's health and well-being. They help strengthen muscles, improve fitness, and reduce the risk of developing many diseases. Regular exercise also improves the functioning of the cardiovascular and respiratory systems, promotes weight loss, improves metabolism and maintains normal blood sugar levels. In addition, exercise improves overall well-being and quality of life.
Keywords: Exercise, health, human body, cardiovascular system, respiratory system, metabolism, musculoskeletal system, weight loss, general well-being, quality of life.